Terapi Kelompok Terapeutik dan Terapi Kognitif Perilaku Efektif Menurunkan Prodroma Remaja dengan Orang Tua Bercerai - Silalahi, Malianti; Daulima, Novy H. C.; Mustikasari, Mustikasari (Jurnal Kesehatan Holistic, 2021)
Adolescent is a growth phase that is quite vulnerable because it is a phase of searching for self-identity. At the stage of adolescent development, the role of parents is needed because it is a place for teens to ask in the process of finding their true identity. Some studies show that parental divorce primarily has a negative impact on adolescent psychology. Adolescent mental health due to divorce parents need to get treatment by knowing the initial signs and symptoms of early psychosis and providing nurses nurses' actions and specialist actions. The writing of this scientific paper explains the results of therapeutic measures of nurses, therapeutic group therapy and cognitive behavioral therapy in reducing the rate of prodroma in adolescents with divorced parents. The method used is case series. Analysis was carried out on 6 teenagers, ages 13-16 years and had divorced parents. Results: Adolescents with divorced parents had increased prodroma rates after receiving therapeutic group therapy, but there was an increase in the achievement of developmental tasks and an increase in cognitive, emotional and psychosocial developmental abilities that were the basis for reducing prodroma. Cognitive behavioral therapy reduces the rate of prodroma in adolescents with divorced parents. The need for further research related to the effectiveness of therapy with more samples.